Sosialisasi Sikap Sportivitas Dalam Permainan Sepakbola Pada Pemuda Dan Remaja Desa Suka Negeri Kecamatan Air Nipis - Ertanto, Dody; Personi, Megi; Ferdiansah, Rahmad; Safitri, Elisa; Azm, Alfi (Jurnal Dehasen Untuk Negeri, 2025)
This Community Service Program (PKM) is a collaboration between lecturers and students of Dehasen Bengkulu University which aims to socialize the importance of sportsmanship in football to teenagers in Suka Negeri Village, Air Nipis District. This activity was motivated by the low awareness of young players towards sportsmanship values ​​such as honesty, respecting opponents, obeying the rules, and accepting defeat with an open heart. Football, which should be a means of character building, often triggers conflict due to a lack of understanding of playing ethics. The method of implementing this activity uses an educational and participatory approach, which includes material counseling, discussions, and soccer match simulations with direct application of sportsmanship. The activity was carried out on June 7, 2025 and was attended by 30 participants, consisting of teenagers, youth leaders. The results of the activity showed that participants experienced an increase in understanding of the concept of sportsmanship, and most began to show a more positive change in attitude when playing. This activity proves that sports can be an effective medium in character education, especially in rural areas. It is hoped that with the synergy between universities and the community, the values ​​of sportsmanship can continue to be instilled and become part of a healthy and constructive playing culture. This activity also strengthens the role of lecturers and students in implementing the Tri Dharma of Higher Education, especially in the aspect of community service.